PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA MELALUI KEPUASAN KERJA DOSEN PADA PTS DI BANJARMASIN - Mahfuzil Anwar (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2017)
Abstract,This study aimed to get empirical evidence about the performance of the organization's culture through job satisfaction of teachers (lecturers), especially on the main task of carrying out the education and teaching.Through the questionnaires to the respondents for variables with indicators Supportive Organization Culture, Innovative and bureaucracy with item 7 statement Job satisfaction with 6 indicators and 18 items with 6 statements and performance indicators and 18 items statement.Through analysis Multivariate (Structural Equation Modeling) SEM, the results showed that there are four hypotheses proposed, namely: 1) Cultural organizations significant effect on job satisfaction, 2) Cultural organizations significant effect on performance, 3) job satisfaction have a significant effect on performance, and 4) organizational culture significantly influence performance through job satisfaction, and the result is all hypothesis otherwise unacceptable.